Systematic review of interventions to reduce problematic alcohol use in men who have sex with men. - Wray, Tyler B; Grin, Benjamin; Dorfman, Leah; Glynn, Tiffany R; Kahler, Christopher W; Marshall, Brandon D L; Van Den Berg, Jacob J; Zaller, Nickolas D; Bryant, Kendall J; Operario, Don (Drug and alcohol review, 2015)
Rates of heavy drinking, alcohol problems and alcohol-related disorders are high among men who have sex with men (MSM) and are an important public health issue. Associations between heavy drinking and human immunodeficiency virus (HIV) acquisition among MSM also suggest that drinking may have more severe and chronic consequences for this population relative to others. Consequently, effective interventions to reduce heavy drinking and alcohol-related risk factors among MSM are needed.